Determinantes dos movimentos migratórios intermunicipais: uma análise nos municípios paranaenses sob a ótica da Hipótese de Tiebout e da Teoria da Condição Financeira - Costa, Ruy Fernandes da Silva (2019)
This research aims to analyze the influence of financial-budgetary and socioeconomic factors on the net migratory rate of the municipalities of Paraná. Among the justifications of this study, we highlight the fact that there is an open gap due to the lack of research involving the financial-budgetary and socioeconomic variables, deepening with the study of the Tiebout Hypothesis and Theory of Financial Condition and its relations with the movements. so that evidence is raised to support future studies. The research, classified as documentary, used a descriptive methodology of quantitative approach and its data were collected exclusively over the internet in the years 2018 and 2019. To fulfill the objective, a sample composed by the 399 municipalities of Paraná in the years 2013 to 2006 was selected. 2017, but due to some missing data, it was reduced to 366 municipalities, which totaled 1,830 observations. The research concluded that the financial-budget variable per capita expenditures and the socioeconomic variables MHDI, GDPM per capita, and the FIRJAN Municipal Development Indexes (employment, income, education and health) exert a positive and significant influence on the net migration rate in the countries. municipalities of Paraná, being factors of attraction of internal migration. On the other hand, the financial-budgetary variable long-term obligations negatively influences the net migration rate, being a factor for migration. Population size, current liquidity and operating position are variables that were not significant in relation to the net migration rate. Municipalities have little autonomy and flexibility to attract migration, due to their dependence on public policies of the state and federal government, especially in relation to their tax management.